Action on Heritage Conservation of Wooden Structures: Enhancing the Cultural Spaces of Pontianak by Reconstruction of a Traditional Malay House - Zain, Zairin; Irwin, Irwin; Andi, Uray Fery (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2023)
Preserving damaged memorial buildings are vital to maintain a cultural identity to be reused and inherited by future generations. Buildings established in the past will overlook that they will be aging and weathering. Wooden construction in Malay traditional houses built more than 100 years ago faces durability issues. Environmental conditions equally make its structure unusable. In addition, its surrounding environment has changed, and the demands for new functions for improving the structure’s condition have become challenges in retrofitting the traditional roles into the current contemporary activities needs. The traditional Malay house in Kampung Bangka, Pontianak, which experienced a transfer of ownership from the original owner to the city government, altered its function from a residential house to a cultural house. Buildings having experienced weathering requires a well-planned reconstruction and re-functioning efforts from the city government. The reconstruction stages and house’s identification process of previous roles are required to accommodate new activities fit for culture and public space. Identification and analysis process carried out to resolve the damaged condition of structural elements of the building to maintain its authenticity as memorials building for the community. Identification is also required to anticipate the new function of the building by providing a new structure or reinforcement to govern the future activities during the operation period of the building. Cultural and structural analysis is carried out to improve the function of the building and the surrounding area into a cultural space that enhances its image as a public space.